Gender bias and inequity holds women back in their conservation careers - James, Robyn; Fisher, Jonathan R. B.; Carlos-Grotjahn, Chelsea; Boylan, Marissa S.; Dembereldash, Baigalmaa; Demissie, Meaza Z.; Diaz De Villegas, Crystal; Gibbs, Bridget; Konia, Ruth; Lyons, Kristen; Possingham, Hugh; Robinson, Cathy J.; et al. (Frontiers in Environmental Science, 2023)
The planet is facing climate and biodiversity loss crises that impact all humanity and yet women remain underrepresented in climate and conservation leadership and decision making. Women report multiple and systemic barriers that limit their contributions to addressing urgent climate and conservation challenges. As one of the world’s largest conservation non-profit organizations, The Nature Conservancy (TNC) provides a case-study for understanding gender disparity for people working in the conservation sector. In 2018, all 1,789 conservation and science staff at TNC were surveyed to understand how they contribute to the organization’s conservation research and decision making. The survey also examined how respondents perceived opportunities and support for career development in conservation, as well as being asked for suggestions to address any gender inequity they had seen or experienced across their careers. Of the 904 responses (490 men and 414 women), results showed that men felt significantly more able to influence conservation decisions than women. Women answered less favorably than men on all questions relating to opportunities for career growth, professional development, as well as pay and benefits. These results align with overall trends in workplaces globally. Of significance, men reported the sector as a more equitable and favorable place for women than women themselves experienced. Our data demonstrates that gender equality (equal representation of men and women) does not automatically mean that women no longer face systemic inequity. Based on our findings, we provide recommendations for conservation and science organizations to improve gender equity, including via workplace and cultural change measures, as well as changes to recruitment, pay transparency and career development policies.